Problems of Art Teaching in Nigerian Secondary Schools System: Implications for Trainers - Adeyanju, 'Lade Joel (2014)
This study looks at the problems associated with the teaching of Fine Arts in Nigerian secondary school system. With the purpose of ameliorating the present situation, the study was conducted through the use of a set of 22 item questionnaire on causes of some of the problems concerning Fine Arts teaching. The population for the study comprised fifty-two (52) experienced Fine Art teachers who were undergoing the Part Time Degree programme of Obafemi Awolowo University between 1994 and 1999.